Life Cycle Assessment of Neodymium-Iron-Boron Magnet-to-Magnet Recycling for Electric Vehicle Motors - Jin, Hongyue; Afiuny, Peter; Dove, Stephen; Furlan, Gojmir; Zakotnik, Miha; Yih, Yuehwern; Sutherland, John W (Environmental science & technology, 2018)
Neodymium-iron-boron (NdFeB) magnets offer the strongest magnetic field per unit volume, and thus, are widely used in clean energy applications such as electric vehicle motors. However, rare earth elements (REEs), which are the key materials for creating NdFeB magnets, have been subject to significant supply uncertainty in the past decade. NdFeB magnet-to-magnet recycling has recently emerged as a promising strategy to mitigate this supply risk. This paper assesses the environmental footprint of NdFeB magnet-to-magnet recycling by directly measuring the environmental inputs and outputs from relevant industries and compares the results with production from “virgin” materials, using life cycle assessments. It was found that magnet-to-magnet recycling lowers environmental impacts by 64–96%, depending on the specific impact categories under investigation. With magnet-to-magnet recycling, key processes that contribute 77–95% of the total impacts were identified to be (1) hydrogen mixing and milling (13–52%), (2) sintering and annealing (6–24%), and (3) electroplating (6–75%). The inputs from industrial sphere that play key roles in creating these impacts were electricity (24–93% of the total impact) and nickel (5–75%) for coating. Therefore, alternative energy sources such as wind and hydroelectric power are suggested to further reduce the overall environmental footprint of NdFeB magnet-to-magnet recycling.